Eficácia da Morinda citrifolia (noni) no tratamento de cães com sintomatologia neurológica infectados pela Ehrlichia canis e pelo vírus da cinomose - TORRES, Mylena Andréa Oliveira (2016)
Canine distemper and ehrlichiosis are two diseases affecting dogs, which have neurological symptomatology. The former is a contagious viral disease, with a high incidence and mortality that affects dogs and other canids; the latter is a bacterial disease highly frequent. The treatment of neurological diseases is based on drug administration, which may act both on etiologic agent as reducing the progression of the disease; or on supportive therapy, in cases of canine distemper. Looking for an alternative treatment for diseases with neurological conditions, low-cost, easy to administrate and with satisfactory effects in the remission of clinical signs, this study aimed to evaluate the effectiveness of Morinda citrifolia (noni) in the treatment of dogs with neurological symptoms caused by canine distemper virus and Ehrlichia canis. To evaluate the effect of M. citrifolia vegetable drug in animals with ehrlichiosis, ten animals were used, divided into two groups, one treated with the standard drug, doxycycline (10 mg/kg, BID, orally) and complex B vitamins (0.2 mg/kg, BID, orally), and the other treated with the experimental protocol (500 mg of M. citrifolia vegetable drug, SID, orally). Thirty days post-treatment, blood collection was made to evaluate hematological parameters. Although noni has led to the improvement of these parameters, especially platelets, animals did not show clinical cure, which demonstrated its inefficacy in the treatment of ehrlichiosis. To evaluate the effect of the vegetable drug in animals with canine distemper, fifteen animals were used, divided into two groups, one treated with the conventional drugs and the other with the experimental protocol. After thirty days, was observed that the animals treated with noni showed remission of clinical signs, demonstrating its efficacy against distemper neurological signs. As the last step of this work, were assessed the lesions in the central nervous system of dogs in an advanced stage of distemper, which were euthanized. Several brain areas of seven dogs were collected (cerebellum, rostral colliculus, caudal colliculus, obex, cerebellar peduncle and telencephalon), to perform histopathological and immunohistochemical analyses. In histopathological analysis was observed that the cerebellar peduncle was the most affected area and that inflammation and demyelination were the major findings. Immunohistochemistry confirmed histopathological results, with markings in all areas of the brain and, contrary to the literature; neurons were the cells that presented more viral particles.